PENENTUAN KADAR KAFEIN DALAM BUNGA, BIJI, KULIT BUAH DAN DAUN KOPI ARABIKA (Coffea arabica) WONOLELO MENGGUNAKAN SPEKTROFOTOMETER UV - Putri, Mega; Beta Ria Erika Marita Dellima (Universitas Kristen Immanuel, 2023)
Arabica coffee is a type of coffee that is widely cultivated in Indonesia. Caffeine is one of the secondary metabolites contained in coffee with various biological benefits. Caffeine belongs to the class of alkaloids of the methylxanthine group. Caffeine is distributed in different parts of the coffee plant in the leaves, cotyledons and flowers. Various studies have proven that the caffeine content in each part of the coffee plant has varying levels. This study aims to determine which part of the Arabica coffee plant comes from Wonolelo, Temanggung with the highest caffeine content. Powder of flowers, leaves, seeds and fruit skins of Arabica coffee were extracted with distilled water and then extracted liquid-liquid with chloroform, the chloroform fraction obtained was evaporated to form crystals containing caffeine. The results were analyzed quantitatively by UV spectrophotometry. The absorbance results were obtained from UV spectrophotometric readings, then the caffeine content in the sample was calculated and analyzed using SPSS software. Quantitative test stated that the highest to the lowest caffeine content were fruit peels of 3.232%, seeds (0.771%), flowers (0.509%), and leaves (0.24%). The results of this study are different compared to previous studies. This can occur due to differences in extraction methods, sample age, roasting conditions, grinding degree, geographical origin, such as growing locations at different altitudes, soil types, rainfall, harvest time, and intensity of exposure to sunlight.